OROFACIAL ORTHOPEDICS: THE SURGERY FIRST METHOD IN ORTHOGNATHIC SURGERY - DIVYA SONI, SOURABH VIPUL, POOJA GANGARE, NEHA GUPTA, SHIVANI BHUYAN, NEELAM DHAKAR (South Eastern European Journal of Public Health, 2025)
The Surgery First method in orthognathic surgery is an evolving approach that prioritizes performing corrective jaw surgery before orthodontic treatment. Traditionally, orthognathic surgery follows a period of orthodontic alignment to optimize dental positioning. However, the Surgery First method aims to accelerate overall treatment by reducing the time spent in orthodontic therapy and achieving rapid skeletal correction. This method has been gaining attention for its potential to shorten treatment duration, improve patient satisfaction, and streamline the management of skeletal discrepancies. The approach requires careful patient selection, as it may not be suitable for all individuals. This review explores the underlying principles of the Surgery First method, its benefits, limitations, and clinical outcomes, highlighting its role as an innovative strategy in orofacial orthopedics and orthognathic surgery